Experimental investigation of the film cooling performance by triangular-shaped thin plates on inclined cylindrical holes - Choi, Jaemun; Choi, Jaehun; Kwon, Hwabhin; Jang, Hoyong; Park, Heesung (Frontiers in Energy Research, 2022)
Experimental investigations have been conducted to improve the cooling effectiveness of film-cooling technology. A multiple row of cylindrical holes at the flat surface was considered by inclining the holes at 35° along the streamwise direction. A low-speed wind tunnel with the main flow speed of 10 m/s was devised to create a cross flow at a Reynolds number of 196167 and five blowing ratios of 0.3, 0.5, 0.7, 1, and 2. The proposed triangular-shaped thin plate and flop at the cylindrical film cooling hole were investigated using flow visualization and thermographic techniques. The resulting cooling performances were also experimentally evaluated and compared with respect to the different film-cooling hole configurations. The typical film cooling hole configuration of cylindrical hole shape shows the cooling effectiveness of 0.1 at blowing ration of 1.0. It should be denoted that this cooling effectiveness is exemplary value of wide range of gas turbine applications. We also experimentally evaluates the cooling effectiveness in order to valid our experimental method. Meanwhile, with triangular-shaped thin plate-flop, the flow detachment is successfully prevented with requiring 8 % increase of discharge coefficient. In addition, the film flow is stable even at the distant downstream, resulting in enhanced cooling performance compared to the cylindrical and triangular-shaped thin plate. Consequently, a 242.7% improvement in film cooling effectiveness can be achieved with a triangular-shaped thin plate-flop than with a cylindrical hole owing to its enhanced film coverage.